Investigating Student's Ability to Ask Question In A Group Discussion of the Eight Year Student of SMP Walisongo Pecangaan Jepara in the Academic Year 2010/2011 - HAMIDI, ALI AKBAR (2011)
The objectives of the research are (1) to describe the students ability in asking questions. (2) to classify the problems faced by the eight year students of SMP Walisongo Jepara to ask Questions. (3) to identify the causes of the problems faced by the eight year students of SMP Walisongo Jepara to ask Questions. The study was done in SMP Walisongo Jepara. As the sample, the writer took 28 students of the eight class. The writer conducted a test to take the data. The test was 10 items about yes/no questions and the other 10 about wh-questions. After analyzing the data, the writer described the result of the study. The writer finds that (1) the capability of the students in asking and answering questions can be divided into three level mastery, they are 8 students got good score or (B), 7 students got fair or (C), while 13 students got D or fail. (2) the problem faced by the students in asking and answering questions are a) most of the students have difficulties in arranging the sentence correctly, b) the students have difficulties in translating the word from English into Indonesian and Indonesian into English, c) most of student have limited vocabulary. (3) the causes of the problems faced by the students are a) the teacher did not motivate the students to improve their reading skill because in teaching process the teacher does not equip reading strategy to motivate the students in improving their asking and answering question, predicting unfamiliar words in the context of the asking and answering questions, etc. b) the students vocabulary and grammar are still limited because in teaching process the teacher usually focuses on the definitions, parts, and questions of the written texts itself so when the students ask and answer questions they cannot comprehend it well. In conclusion, the students' ability in asking and answering questions at SMP Walisongo Jepara is fair.